Analysis on Dynamic Decision-Making Model of the Enterprise Technological Innovation Investment under Uncertain Environment - Yong Long; Hongwei Wu; Ke Qiucheng Zhou (Journal of Applied Mathematics)
Under the environment of fuzzy factors including the return of market, performance of product, and the demanding level of market, we use the method of dynamic programming and establish the model of investment decision, in technology innovation project of enterprise, based on the dynamic programming. Analysis of the influence caused by the changes of fuzzy uncertainty factors to technological innovation project investment of enterprise.